Controller Design for a Two-loop Missile Autopilot in Pitch Plane (International Journal of Engineering and Computer Science, 2015)
This research work is an attempt towards achieving an approach for designing PI and PID controllers for a two loop missile autopilot system in pitch plain. A two loop autopilot configuration has been chosen which is characterized by a dynamics involving non-minimum phase zero. A systematic methodology for linear design in frequency domain of lateral autopilot for a class of guided missiles has been carried out. The present work utilizes the autopilot configuration with one accelerometer and one rate gyro. The configuration in pitch plain for the two loop autopilot system has been illustrated. The present work includes a study on plant uncertainties.